Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3340/jkns.2017.0202.001
|View full text |Cite
|
Sign up to set email alerts
|

Protected versus Unprotected Carotid Artery Stenting : Meta-Analysis of the Current Literature

Abstract: ObjectiveTo compare peri-operative any symptomatic stroke after carotid angioplasty and stenting (CAS), based on the application or absence of a cerebral protection device.MethodsA systematic literature review using PubMed, Embase, and the Cochrane Central was done across an online data base from January 1995 to October 2016. Procedures which were performed due to carotid dissection or aneurysm, procedures using covered stents or conducted in an emergency, were excluded. The primary endpoint was perioperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The Trim-and-Fill method was performed further to estimate the number and outcome of missing studies. [14][15][16] The comprehensive meta-analysis (CMA) software (CMA v2.2.064; Biostat, Englewood, NJ, USA) was used for all the above, with statistical significance defined as P<0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Trim-and-Fill method was performed further to estimate the number and outcome of missing studies. [14][15][16] The comprehensive meta-analysis (CMA) software (CMA v2.2.064; Biostat, Englewood, NJ, USA) was used for all the above, with statistical significance defined as P<0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent randomized controlled trials (RCTs) 2 revealed no association between anesthesia type and clinical outcomes. Löwhagen Hendén et al 2 reported no differences in early neurologic improvement (NIHSS score shift within 24 hours after intervention, 9 [4][5][6][7][8][9][10][11][12][13][14][15][16][17] in GA vs. 8 [2.5-13] in CS; P=0.272) and good outcomes at 3 months (n=19, 42.2% in GA vs. 18, 40.0% in CS; P=1.00). Schönenberger et al 5 also reported no neurologic improvement according to anesthesia type in acute anterior circulation stroke after thrombectomy.…”
Section: Intrudoctionmentioning
confidence: 99%
“…The derivation cohort was obtained from the stroke database of the Chuncheon Sacred Heart Hospital. The cohort is a prospective and observational project in the regional center of the district of Chuncheon city, the capital city of Gangwon Province in Korea 11 , 29 31 . In this database, we enrolled SAH patients with the following conditions: (1) adult SAH patients aged above 18 years; and (2) SAH due to ruptured aneurysm associated with saccular appearance.…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were 1) fusiform, dissected, traumatic or infectious aneurysms and 2) patients with concomitant other cerebrovascular diseases. Patients who met the following criteria were selected as controls : 1) patients who underwent radiologic tests for headache or medical check-ups with 2) no familial history of IA or SAH among the first-degree relatives [ 6 , 9 , 12 , 13 , 18 ].…”
Section: Methodsmentioning
confidence: 99%